Barrows and gilts respond differently as experimental models for Escherichia coli challenge during the nursery phase - Oliveira, Ana Clara Rodrigues de; Carnino, Bruno Braga; Guimarães, Eduarda Buck Bernardes; Alves, Laya Kanan Silva; Lima, Tarik Mohallem Pereira; Schinckel, Allan Paul; Garbossa, Cesar Augusto Pospissil (Acta Scientiarum. Animal Sciences, 2025)
The objectives of this study were to evaluate the effect of Escherichia coli (E. coli) F4 challenge in nursery piglets, and to develop an experimental model to be used in research. Ninety-six weaned piglets were divided in a 2 x 2 factorial design consisting of E. coli challenge (challenged or not challenged) and sex (barrows or gilts). Pig growth performance, fecal score, blood count, intestinal morphometry, and cecal content (microbiological and short-chain fatty acid analysis) data were collected and analyzed. Pigs in the non-challenged treatment had 6% greater average daily gain during day 8-28 (the period in which the health challenge was administered) and 1.2% greater average daily feed intake in over the entire experiment, when compared to challenged pigs. Gilts in the non-challenged group had a higher villus: crypt ratio when compared to piglets in the challenged group. These findings indicate that the pathogen challenge using Escherichia coli F4 strains, especially in gilts, proved to be an effective method to reproduce commercial health challenges in the first two weeks postweaning and may be used in experimental models.